2023
DOI: 10.3892/ol.2023.13801
|View full text |Cite
|
Sign up to set email alerts
|

HnRNPAB is an independent prognostic factor in non‑small cell lung cancer and is involved in cell proliferation and metastasis

Abstract: Heterogeneous nuclear ribonucleoprotein A/B (hnRNPAB) is an RNA binding protein that is closely associated with the biological function and metabolism of RNA, which is involved in the malignant transformation of various tumor cells. However, the role and mechanisms of hnRNPAB in non-small cell lung cancer (NSCLC) are still unclear. In the present study, the expression levels of hnRNPAB in NSCLC and normal tissues were analyzed using the human protein atlas database and UALCAN database. The clinical significanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…The FAM53B gene, implicated in Wnt signaling, is deregulated in T cell dysfunction, and found to truncated in the bone marrow tissue from acute lymphoblastic leukemia (31,32,33). HNRNPAB is an RNA binding protein documented as a prognostic biomarker in several solid tumors (34,35) and is considered as an important biomarker and therapeutic target (36). We also showed that the levels of lower levels of HSD17B13, KANSL 1L, and LBR predicted worse survival rates.…”
Section: Discussionmentioning
confidence: 99%
“…The FAM53B gene, implicated in Wnt signaling, is deregulated in T cell dysfunction, and found to truncated in the bone marrow tissue from acute lymphoblastic leukemia (31,32,33). HNRNPAB is an RNA binding protein documented as a prognostic biomarker in several solid tumors (34,35) and is considered as an important biomarker and therapeutic target (36). We also showed that the levels of lower levels of HSD17B13, KANSL 1L, and LBR predicted worse survival rates.…”
Section: Discussionmentioning
confidence: 99%